Evaluation of a known breast cancer using an abbreviated breast MRI protocol: Correlation of imaging characteristics and pathology with lesion detection and conspicuity. Issue 4 (April 2016) - Heacock, Laura; Melsaether, Amy N.; Heller, Samantha L.; Gao, Yiming; Pysarenko, Kristine M.; Babb, James S.; Kim, Sungheon G.; Moy, Linda
Highlights: Abbreviated breast MR has a high detection rate for DCIS and invasive carcinoma. T2-weighted imaging did not alter detection but increased lesion conspicuity. The majority of missed cancers were low-grade with low initial enhancement ratio. Abstract: Objective: This study evaluates use of an abbreviated magnetic resonance imaging protocol with T2-weighted imaging in detecting biopsy-proven unifocal breast cancer. Materials and methods: This is an institutional review board approved retrospective study of patients with biopsy-proven unifocal breast cancer (88% invasive; 12% in situ) undergoing magnetic resonance imaging. In three separate sessions, three breast imagers evaluated (1) T1-weighted non-contrast, post-contrast and post-contrast subtracted images, (2) T1-weighted images with clinical history and prior imaging, and (3) T1-weighted images and T2-weighted images with clinical history and prior imaging. Protocols were compared for cancer detection, reading time and lesion conspicuity. An independent breast radiologist retrospectively analyzed initial enhancement ratio of cancers and retrospectively reviewed lesion morphology and final pathology. Results: All 107 cancers were identified at first protocol by at least one reader; five cancers were missed by either one or two readers. One cancer was missed by one reader at protocols two and three. Mean percentage detection for protocol one was 97.8%; protocol two, 99.4%, protocol three, 99.4%. T2-weighted images did not alter cancer detection but increased lesion conspicuity for 2/3 readers. 3/5 missed lesions were low grade cancers. Initial enhancement ratio was positively associated with increasing tumor grade ( p = 0.031) and pathology ( p = 0.002). Reader interpretation time decreased and lesion conspicuity increased as initial enhancement ratio increased. Conclusion: Abbreviated magnetic resonance imaging has high rate of detection for known breast cancer and short interpretation time. T2 weighted imaging increased lesion conspicuity without altering detection rate. Initial enhancement ratio correlated with invasive disease and tumor grade.